A scoping review of the feasibility, usability, and efficacy of digital interventions in older adults concerning physical activity and/or exercise - Ethan C. J. Berry; Nicholas F. Sculthorpe; Ashley Warner; James D. Mather; Nilihan E. M. Sanal-Hayes; Lawrence D. Hayes (Frontiers in Aging)
Background:The global population is aging, leading to significant health challenges among older adults, such as reduced muscle mass, increased risks of dementias, and chronic diseases. Physical activity (PA) is crucial for maintaining health and wellbeing in this demographic, yet participation tends to decrease with age due to various barriers. Digital technologies, including mobile health (mHealth) interventions, show promise in promoting PA among older adults, though their adoption remains limited due to intrinsic and extrinsic challenges.ObjectivesThis scoping review aimed to systematically map existing evidence on digital PA interventions for older adults, assessing feasibility, usability, and efficacy, whilst providing recommendations for future research and practice.Eligibility criteriaOriginal investigations concerning digital interventions in older adults (≥60 years of age) focusing on physical activity and/or exercise were considered. Sources of evidence: Four electronic databases [MEDLINE, CINAHL Ultimate, Scopus and Cochrane Central Register of Controlled Trials (CENTRAL)] were searched.MethodsA scoping review was conducted using the scoping review methodological framework. Review selection and characterisation were carried out by two independent reviewers.ResultsThe 34 included studies were published between 2005 and 2023 across Europe, North America, Asia, and Oceania. Participants varied from healthy to frail individuals, with some diagnosed with dementia or cognitive impairment. Interventions were most commonly delivered via exergames, tablet apps, and videoconferencing. The most common exercise program type was multicomponent. Most studies assessed efficacy, feasibility, and usability, with many using a combination of these measures. Reminders were commonly utilised to enhance engagement through various digital and non-digital methods.ConclusionThere was a notable lack of mobile health (mHealth) studies in the literature, with most research focusing on exergame and tablet interventions. More research on smartphone apps, particularly for muscle strengthening, is needed, and the growing ease of app development may drive innovation and research. Digital interventions are generally feasible, usable, and effective for older adults, offering a promising, scalable approach for promoting PA. This review identified several valuable lessons from the existent literature for future developments.